Hypertensive Disorders of Pregnancy: A Systematic Review of International Clinical Practice Guidelines - Gillon, Tessa E. R.; Pels, Anouk; von Dadelszen, Peter; MacDonell, Karen; Magee, Laura A. (PloS one, 2014)
Clinical practice guidelines (CPGs) are developed to assist health care providers in decision-making. We systematically reviewed existing CPGs on the HDPs (hypertensive disorders of pregnancy) to inform clinical practice. MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials, Cochrane Methodology Register, Health Technology Assessments, and Database of Abstracts of Reviews of Effects (Ovid interface), Grey Matters, Google Scholar, and personal records were searched for CPGs on the HDPs (Jan/03 to Nov/13) in English, French, Dutch, or German. Of 13 CPGs identified, three were multinational and three developed for community/midwifery use. Length varied from 3-1188 pages and three guidelines did not formulate recommendations. Eight different grading systems were identified for assessing evidence quality and recommendation strength. No guideline scored ≧80% on every domain of the AGREE II, a tool for assessing guideline methodological quality; two CPGs did so for 5/6 domains. Consistency was seen for (i) definitions of hypertension, proteinuria, chronic and gestational hypertension; (ii) pre-eclampsia prevention for women at increased risk: calcium when intake is low and low-dose aspirin, but not vitamins C and E or diuretics; (iii) antihypertensive treatment of severe hypertension; (iv) MgSO4 for eclampsia and severe pre-eclampsia; (v) antenatal corticosteroids at <34 wks when delivery is probable within 7 days; (vi) delivery for women with severe pre-eclampsia pre-viability or pre-eclampsia at term; and (vii) active management of the third stage of labour with oxytocin. Notable inconsistencies were in: (i) definitions of pre-eclampsia and severe pre-eclampsia; (ii) target BP for non-severe hypertension; (iii) timing of delivery for women with pre-eclampsia and severe pre-eclampsia; (iv) MgSO4 for non-severe pre-eclampsia, and (v) postpartum maternal monitoring. Existing international HDP CPGs have areas of consistency with which clinicians and researchers can work to develop auditable standards, and areas of inconsistency that should be addressed by future research.